Quality and Effectiveness in Electronic Tax Filling: A Study of Tax-Payer Satisfaction - Prakosa, Fajar; Pertiwi, Asri (International Journal of Technology And Business, 2018)
This study aims to analyze the effectiveness of e-filling application by tax-payers. Online tax system has received a great attention globally through the development of information technology, which affects the tax administration system. The theory adopted IS Success DeLone and McLean using three variables to measure the effectiveness of e-filling include user satisfaction, information quality, system quality, and service quality. Data collected through surveys conducted to taxpayers who have used e-filling. PLS SEM and path analysis was applied to test the influences of the quality antecedents to user satisfaction with IS. Path coefficients provided a measure of the importance of each quality antecedent.  Information quality, System quality, and service quality are  positively associated with taxpayer satisfaction